EFFECTS OF COLORS IN LIFE (SUN RAYS): रंगों का जीवन में प्रभाव (सूर्य किरणें) - Malaviya, Shraddha (International Journal of Research -GRANTHAALAYAH, 2014)
Dr. Lebis has written that there is a very close relationship between incense and digestion. If the sun rays do not fall on man or any other creature every day, then its digestion and equation power is impaired. Spuran and human life have a close relationship between them. Life is related to light power and its splendor, not protein, white matter, hydrogen, carbon or heat. Like the sky and air element, the light element is also very subtle. The colors of the colors we see in the lush green area of ​​nature, all of this is the illusion of the sun’s colorful rays. Color illuminated in light is not only beautiful to the eyes, but is also a life color. The rays of the sun have a lasting effect on the living world. This is the basis of Sun ray therapy. By keeping water in colored bottles, the effect of light also changes and different qualities are produced in it. डाॅ. लेबिस ने लिखा है कि धूप और पाचन की क्रियाओं में बड़ा घनिष्ठ सम्बंध हैं। यदि मनुष्य या अन्य किसी प्राणी पर प्रति दिन सूर्य किरणें नहीं पड़ती, तो उसकी पाचन और समीकरण षक्ति क्षीण हो जाती है। स्फुरण तथा मानव जीवन इन दोनों का परस्पर घनिष्ठ सम्बंध है। जीवन का सम्बंध प्रकाष षक्ति तथा उसके वर्ण वैभव से है, न कि प्रोटीन, ष्वेत सार, हाइड्रोजन, कार्बन अथवा उष्णांक से। आकाश और वायु-तत्व की भाँति प्रकाष तत्व भी अत्यंत सूक्ष्म है। प्रकृति के हरे भरे प्रषस्त अंचल में हम जो अनेक रंगों के चित्र देखते है, यह सब सूर्य की सतरंगी किरणों की ही माया है। प्रकाष में अन्तर्निहित रंगीनी केवल नेत्रों को ही सुन्दर प्रतीत नहीं होती प्रत्युत जीवन रंजक भी है। सूर्य की किरणों का प्राणी जगत पर स्थायी प्रभाव पड़ा है। सूर्य किरण चिकित्सा का यही मूलधार है। रंगीन बोतलों में पानी रखने से प्रकाष का प्रभाव भी बदलता रहता है और उसमें भाँति- भाँति के गुण उत्पन्न हो जाते हैं।